MiR-128-3p suppresses tumor proliferation and metastasis via targeting CDC6 in hepatocellular carcinoma cells. (October 2021) - Shi, Yu; Yan, Fuguo; Wang, Fangping; Pan, Linfeng
Highlights: MiR-128-3p may have inhibitory effect on cell proliferation, migration, invasion and EMT progress of HCC. CDC6 may be the promoter of cell viability, migration, invasion and EMT progress in HCC. MiR-128-3p may suppress HCC cell proliferation and metastasis progress via targeting CDC6. Abstract: Background: MicroRNAs (miRNAs) are known to be involved in the pathogenesis of various cancers. The present study devotes efforts to discover the role of miR-128-3p in hepatocellular carcinoma (HCC). Methods: MiR-128-3p and cell division cycle 6 (CDC6) expressions in HCC tissue (n = 50) and adjacent normal tissue (n = 50) were detected by quantitative real-time polymerase chain reaction (qRT-PCR). MTT assay and flow cytometry were applied to measure the viability and cell cycle distribution of HuH7 and HCCLM3 cells, respectively. The potential binding sites of miR-128-3p on CDC6 were predicted with Targetscan 7.2 and confirmed by dual-luciferase reporter assay. Expression analysis of CDC6 and survival analysis in HCC were performed by GEPIA2. Wound healing and Transwell assays were used to detect HCC cell migration and invasion, respectively. Expressions of miR-128-3p and epithelial-mesenchymal transition (EMT)-related proteins (MMP2, MMP9, E-Cadherin, N-Cadherin and Vimentin) were quantified using qRT-PCR and western blot, respectively. Results: MiR-128-3p mRNA expression was lower in HCC tissue than in adjacent normal tissues. HCC cell viability was suppressed and cell cycle was arrested in G0/S phase by miR-128-3p mimic. CDC6 was targeted by miR-128-3p and had higher expression in HCC tissue. The promotive effects of overexpressed CDC6 on HCC cell viability, migration and invasion were reversed by up-regulating miR-128-3p. And the effects of overexpressed CDC6 on inhibiting E-Cadherin expression yet promoting MMP2, MMP9, N-Cadherin and Vimentin expressions in HCC cells were reversed by up-regulating miR-128-3p. Conclusion: MiR-128-3p may suppress HCC cell proliferation and metastasis via targeting CDC6.